Phonological processing skills in specific language impairment - Claessen, Mary; Leitão, Suze; Kane, Robert; Williams, Cori (Informa Healthcare, 2013)
In order to provide effective intervention for children with specific language impairment (SLI), it is crucial that there is an understanding of the underlying deficit in SLI. This study utilized a battery of phonological processing tasks to compare the phonological processing skills of children with SLI to typically-developing peers matched for age or language. The children with SLI had significantly poorer performance than age-matched peers on measures of phonological representations, phonological awareness, rapid automatized naming, phonological short-term memory, and one measure of working memory. Of particular significance, the SLI group also demonstrated significantly weaker performance than language-matched peers on one measure of phonological representations, and one measure of working memory. The findings provide some support for a phonological processing account of SLI and highlight the utility of using tasks that draw on a comprehensive model of speech processing to profile and consider children's phonological processing skills in detail.